Comparative study on the libido, semen quality and fertility of Brahman cross, Holstein Friesian cross and Red Chittagong breeding bulls: Libido, semen quality and fertility of breeding bulls - Islam, MM; Apu, AS; Hoque, SAM; Ali, MY; Karmaker, S (Bangladesh Journal of Animal Science, 2018)
The present study was undertaken to compare the performance of 8 (eight) breeding bulls of three different genetic groups such as Brahman × local (4 bulls), Holstein Friesian × local (2 bulls) and Red Chittagong (2 bulls) based on libido, semen quality and fertility. Semen parameters were evaluated from 30 ejaculates from each bull and fertility rate was calculated based on 60-days non-return rate via AI using these semen samples. Genetic group of breeding bulls had significant (p<0.05) effect on libido. Holstein Friesian cross breeding bulls showed significantly (p<0.05) highest libido (3.77±0.15) followed by Brahman cross (3.38±0.07) and lowest in Red Chittagong (RC) breeding bulls (2.96±0.11). Semen attributes also significantly affected by the different genetic group of bulls. Holstein Friesian crossbred breeding bulls with highest libido provided significantly (p<0.01) highest volume of semen (5.63±0.16 ml) per ejaculate, progressive motility (74.73±0.76%), live sperm (84.18±0.62%) and normal sperm (83.18±1.47%) whereas these parameters were significantly (p<0.01) lowest in RC breeding bulls. Moreover, libido showed a strong and positive correlation with all these semen parameters. The fertility rate was also significantly highest (p<0.05) in Holstein Friesian crossbred breeding bull (63.67±1.46%), followed by Brahman crossbred (58.86±1.05%) and lowest in RC breeding bulls (53.42±0.85%). These results suggested that semen quality is positively correlated with the libido of breeding bulls and quality is important for higher fertility. Therefore, libido as well as semen quality evaluation may be important criteria to discard the breeding bulls with poor fertility in an AI program. Bang. J. Anim. Sci. 2018. 47 (2): 61-67